2016
DOI: 10.1038/srep37310
|View full text |Cite
|
Sign up to set email alerts
|

The androgen-induced protein AIbZIP facilitates proliferation of prostate cancer cells through downregulation of p21 expression

Abstract: Androgen-Induced bZIP (AIbZIP) is structurally a bZIP transmembrane transcription factor belonging to the CREB/ATF family. This molecule is highly expressed in androgen-sensitive prostate cancer cells and is transcriptionally upregulated by androgen treatment. Here, we investigated molecular mechanism of androgen-dependent expression of AIbZIP and its physiological function in prostate cancer cells. Our data showed that SAM pointed domain-containing ETS transcription factor (SPDEF), which is upregulated by and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 43 publications
2
23
0
Order By: Relevance
“…32 In addition, Cui et al reported that androgeninduced bZIP, belonging to the CREB/ATF family, facilitated proliferation of prostate cancer cells through downregulation of CDKN1A expression. 34 Our present study demonstrated that the expression of CDKN1A was regulated by CREB in HCC cells. Furthermore, HRH3 downregulated the expression of CDKN1A via inhibiting the phosphorylation of CREB in HCC cells.…”
Section: Discussionsupporting
confidence: 56%
“…32 In addition, Cui et al reported that androgeninduced bZIP, belonging to the CREB/ATF family, facilitated proliferation of prostate cancer cells through downregulation of CDKN1A expression. 34 Our present study demonstrated that the expression of CDKN1A was regulated by CREB in HCC cells. Furthermore, HRH3 downregulated the expression of CDKN1A via inhibiting the phosphorylation of CREB in HCC cells.…”
Section: Discussionsupporting
confidence: 56%
“…Oestrogen plays an important role in the development and physiology of the normal breast as well as in breast cancer cell proliferation. CREB3L4 has been reported to be highly expressed in sex-related cancers, including prostate, endometrium and uterine cancers [13]. In our experiment, CREB3L4 expression was upregulated in both oestrogen receptorpositive and TNBC cell lines.…”
Section: Discussionsupporting
confidence: 56%
“…As mentioned before, five CREB3 subfamily members have been identified [13]. First, we analysed the differences in the transcription levels of these genes between tumour and normal tissues in multiple types of cancer obtained from the online ONCOMINE database.…”
Section: The Transcription Levels Of Creb3 Subfamily Members In Bcmentioning
confidence: 99%
See 2 more Smart Citations